Supernovae, by Chandra and XMM-Newton - Eric M. Schlegel (Universe)
X-ray emission from supernovae can arise from multiple interactions during their evolution. The immediate explosion is sufficiently energetic to generate X-rays; so, too, is the impact of the shock as it runs into circumstellar matter from earlier mass loss phases. A considerable range of physics is on display during the evolution of such X-ray emission. This paper reviews some of the results of observing supernovae obtained by XMM-Newton and Chandra over the past 25 years. Each satellite has contributed significantly to the collection of observations and to our increased understanding of supernovae.